The dual nature of constraints on foreign worker participation in sports and physical activity in South Korea during COVID-19 - Na, Dongkyu; Park, Mihwa (Frontiers in Sports and Active Living, 2023)
This study provides a different understanding of the constraints imposed by the pandemic and the official and unofficial restrictions that accompanied it. It is an empirical effort demonstrating that the pandemic's effects are not purely negative, but rather, also helped to produce positive and productive practices that draw upon both the inhibiting and enabling features of the constraints it triggered. Engaging with “productive power” in Foucault by considering constraints as practices that both inhibit and enable, the empirical goal of this paper is to explore how pandemic-related constraints on sports and physical activity prohibit foreign worker participation in sports and physical activity. It also examines how the constraints encourage them to pursue an active life in new and unique ways. To achieve this goal, the paper examines the South Korean context, particularly unskilled foreign workers with E-9 visas for non-professional employment in the fishing, farming, and manufacturing industries and their involvement in sports and physical activity during the COVID-19 pandemic. The findings address three “inhibitors” that specifically prevented foreign workers from getting actively involved, then demonstrate that explicit restrictions on sports and physical activity can be transformed into four “enablers” that encouraged foreign workers to participate. The conclusion offers critical reflections on Foucault's “ethical subject,” followed by the limitations and implications of the study.